Predicting outcome in patients under extracorporeal membrane oxygenation due to cardiogenic shock through dynamic change of lymphocytes and interleukins. (June 2015) - Hong, Tsai-Hsia; Hu, Fu-Chang; Kuo, Shuenn-Wen; Ko, Wen-Je; Chow, Lu-Ping; Hsu, Li-Ming; Huang, Shu-Chien; Yu, Sung-Liang; Chen, Yih-Sharng
Abstract: Objectives: Peripheral blood parameters implicating the irreversible damages of cardiogenic shock under extracorporeal membrane oxygenation (ECMO) support patients were investigated. Methods: The blood was collected from 23 cardiogenic shock cases at the time of ECMO installation, and 2, 6, 12, and 24 h after oxygenation. Plasma levels of IL-2, IL-6, IL-7, IL-8, IL-10, IFN-γ, MCP-1, and carbonic anhydrase IX (CA IX) were determined by ELISA. Reactive oxygen species were measured by luminol and lucigenin and leukocyte subpopulations were analyzed by flow cytometry. Generalized additive models (GAMs) were performed to identify the death ranges of every variable and the variables were further discretized at each time point. The combination of predictors was selected from both original and discretized covariates by the generalized linear model (GLM) at each time point. Results: Plasma IL-10 level was the most distinct biomarker between survivors and non-survivors after oxygenation. IL-10 sequentially partnered with IL-6, IL-7, and lymphocyte percentage at 2 h, with CD3 + CD4 + T cells at 6 h, with CA IX at 12 h, and CD3 + T lymphocytes at 24 h predicted death with AUCs 1.000, 0.975, 0.992, and 0.992, respectively. Conclusions: Combination of the GAM plots and GLM models overcame the complexity of different disease categories. The systemic irreversible damages from cardiogenic shock ECMO cases might be detected from several peripheral blood parameters.